Penyelesaian Pembiayaan Bermasalah Akad Murabahah pada Bank Pembiayaan Rakyat Syariah Patriot Bekasi - Merlin Dewi Ariska; Dina Fitrisia septiarini (Universitas Airlangga, 2019)
This study aims to find out dispute settlement mechanism of the financing problem of murabahah contracts at Islamic Rural Bank or BPRS Patriot Bekasi. The research is conducted in a descriptive qualitative approach with the case study method. Informants determined using snowball sampling, and, data collection techniques using interviews, documentation, and observation. The results are analyzed by reducing data, presenting data, and making conclusions. The results of this study indicate that the financing problem of murabahah contracts at Islamic Rural Bank or BPRS Patriot Bekasi is solved carried out by implementing strategies that are conducting accurate analysis, intensive monitoring, and employee training. Meanwhile, the procedure was carried out, and even the financing problem still exists, it will be handled it will handle with preventive action (rescheduling), claims on insurance, curative actions by executing guarantees, management assistance, billing by third parties. But this method has never done by the Islamic Rural Bank Patriot Bekasi and write off, as well as the final write off.Keywords: Financing problem, rescheduling, executing guarantees, write off